Role of the host in virus assembly: cloning of the Escherichia coli groE gene and identification of its protein product. - Hendrix, R W (1978)
Correct assembly of the heads of bacteriophages lambda and T4 requires the function of the groE gene of the Escherichia coli host. We have isolated a transducing derivative of lambda, called lambda gt-Ec.groE, that carries a functional copy of the groE gene. Unlike wild-type lambda, this phage is able to form plaques on hosts with a mutant groE gene. We have isolated an amber mutation in the groE gene carried by the phage, and this has made it possible to identify the groE product as a protein of molecular weight 65,000. In the phage, the groE gene is under the control of an early phage promoter.